Comparing functional MRI protocols for small, iron‐rich basal ganglia nuclei such as the subthalamic nucleus at 7 T and 3 T. Issue 6 (27th March 2017) - de Hollander, Gilles; Keuken, Max C.; van der Zwaag, Wietske; Forstmann, Birte U.; Trampel, Robert
Abstract: The basal ganglia (BG) form a network of subcortical nuclei. Functional magnetic resonance imaging (fMRI) in the BG could provide insight in its functioning and the underlying mechanisms of Deep Brain Stimulation (DBS). However, fMRI of the BG with high specificity is challenging, because the nuclei are small and variable in their anatomical location. High resolution fMRI at field strengths of 7 Tesla (T) could help resolve these challenges to some extent. A set of MR protocols was developed for functional imaging of the BG nuclei at 3 T and 7 T. The protocols were validated using a stop‐signal reaction task (Logan et al. [1984 ]: J Exp Psychol: Human Percept Perform 10:276–291). Compared with sub‐millimeter 7 T fMRI protocols aimed at cortex, a reduction of echo time and spatial resolution was strictly necessary to obtain robust Blood Oxygen Level Dependent (BOLD) sensitivity in the BG. An fMRI protocol at 3 T with identical resolution to the 7 T showed no robust BOLD sensitivity in any of the BG nuclei. The results suggest that the subthalamic nucleus, as well as the substantia nigra, red nucleus, and the internal and external parts of the globus pallidus show increased activation in failed stop trials compared with successful stop and go trials. Hum Brain Mapp 38:3226–3248, 2017 . ©2017 Wiley Periodicals, Inc.